Corticosteroids for Acute Respiratory Distress Syndrome - Guglielmi, Riccardo; Campanella, Antonio; Villar, Jesús; Torres, Antoni; Ferrando, Carlos (Seminars in Respiratory and Critical Care Medicine, 2025)
Acute respiratory distress syndrome (ARDS) remains a heterogeneous and a major challenge disease process despite five decades of study. Emerging translational data delineate three overlapping phases: exudative, proliferative, and fibroproliferative, each driven by distinct immune–mechanical pathways and potentially modifiable by glucocorticosteroids (GC) modulation. Contemporary clinical randomized trials and meta-analyses indicate that early (≤72 hours) administration of systemic GCs at receptor-saturating doses (e.g., dexamethasone from 20 to 10 mg/day, or methylprednisolone 1–2 mg/kg/day) accelerates resolution of pulmonary edema, shortens mechanical ventilation duration, and improves intensive care survival, while prolonged tapering regimens are required once fibroproliferation is established. Conversely, delayed initiation (>14 days), viral pneumonitis with high viral load, recent surgical anastomosis, or uncontrolled fungal coinfection constitute “red flags” in which GCs might increase mortality. Latent-class analyses—a statistical modeling approach in which multivariable data are reduced to indirectly observed (latent) variables—identified two (hyper- and hypoinflammatory) ARDS phenotypes that likely might respond differentially to GC exposure, although we lack validation studies. Therefore, it seems that biomarker-guided precision therapy is poised to replace the historical one-size-fits-all approach. This narrative review integrates epidemiology, pathobiology, pharmacology, and clinical evidence to provide a phase-specific, phenotype-directed framework for GC use in ARDS and outlines future research priorities aimed at harmonizing molecular endotyping with dose, timing, and tapering strategies.
Keywords: acute respiratory distress syndrome; corticosteroids; lung inflammation; systemic inflammation; outcome; organ dysfunction